The Intellectual in Kingsley Amisâ€™s Lucky Jim: A Bourdieusian Perspective - Dastjerdi, Zahra Baraani; Pirnajmuddin, Hossein (Richtmann Publishing, 2012)
Lucky Jim (1954), Kingsley Amisâ€™s debut novel, is a comic, campus fiction, in which Jim Dixon, a member of the new alienatededucated generation, is striving for a position at a university which is still run by the upper-class professors. This masterpiece of Amishas generally been approached from two perspectives: either as an epitome of a new voice in literature (Amis as a member of the AngryYoung Menâ€™s group, for instance) or as an illustration of different literary aspects (a revival of the picaresque in fiction, for instance).However, the central issue of the conflict between the protagonist and the academia has not been adequately addressed. Drawing onPierre Bourdieuâ€™s key concepts and theories, this paper attempts to turn the focus on the roots of this conflict. Bourdieu believes that inevery given â€œfield: the agents compete over positions by fighting over different â€œcapitalsâ€; the ones who occupy a higher degree of capitaloccupy better positions within the field, which would lead to â€œsymbolic capitalâ€. The Welches, representing the upper-middle-class andacademic pseudo-intellectualism own more cultural, economic and social capital which gives them power. The paper examines themodality of the relationship between such capital and power, especially in the field of education, as exemplified by Amisâ€™s novel.